One step forward, two steps back? Consultant influence on local economic development policy in Canada. (7th January 2019) - Cleave, Evan; Arku, Godwin; Chatwin, Merlin
Abstract: Cities are increasingly outsourcing economic development policy advisory and development to private consultants. To explore the role and influence of consultants, this study undertook a systematic examination of the economic development policy documents of 41 cities in the Province of Ontario, Canada. The findings of this study indicate that a small handful of consultants are key actors in economic development policy advisory in Ontario. The policy documents authored by consultants tend to be similar in style, scope, and language; and from a policy perspective, there is convergence of policy as cities are recommended the same economic development strategies.